A Comparative Analysis of the use of First-Person Pronouns in Chinese and Thai - Denonpho, Montree; Chokewinyoo, Nicha; Pewdum, Artidtaya; Fengxian, Luo; Dongyan, Wu (Mandarinable: Journal of Chinese Studies, 2000)
In modern Chinese, the use of first-person pronouns has gone through a process from complex to simple, and finally mainly uses “我”. However, although the first-person pronouns in Thai have also undergone historical development, they are diversified in forms and complicated in use. Different words are often used according to the differences in the speaker’s age, social status, gender and so on. From the perspective of morphology, singular and plural, and grammatical comparison, this paper takes the first-person pronouns as the discussion object, aiming to summarize and compare the similarities and differences of first-person pronouns between Chinese and Thai. Such different use of personal pronouns has certain theoretical significance and reference value for cross-cultural language communication.